Pengaruh Keselamatan Dan Kesehatan Kerja (K3) Dan Disiplin Kerja Terhadap Kinerja Karyawan Pt Perkebunan Nusantara Iii Sukamaju Sukabumi - Hadi, M. Sofyan; Ramdani, Danny (Peneliti.net, 2024)
This study aims to determine the effect of Occupational Safety and Health (K3) and Work Discipline on Employee Performance at PT Perkebunan Nusantara III. The research method used in this research is descriptive verification method with a quantitative approach. The population in this research is 334 employees and the resulting sample is 182 respondents. The sampling technique is using proportionate stratified random sampling, where sampling is done by knowing in advance the number of employees in each division, which then determines the sample for each division at PT Perkebunan Nusantara III. The analysis used in this research is path analysis. The results showed that the description for Occupational Safety and Health (K3), Work Discipline, and Employee Performance at PT Perkebunan Nusantara III was considered good. The relationship between Occupational Safety and Health (K3) and Work Discipline has a strong relationship that is equal to 0.499. There is a partial effect of Occupational Safety and Health (K3) on Employee Performance of 12.2%. There is a simultaneous influence of Occupational Safety and Health (K3) and Work Discipline on PT Perkebunan Nusantara III Employee Performance of 31.9% while the remaining 68.1% is influenced by other variables not examined in this study.